PENYEIMBANGAN IMUNITAS LANSIA DENGAN SOSIALISASI IMUNOMODULATOR ALAM DAN PEMBERIAN SUPLEMEN - Linawati, N.M.; Rai Widarta, I.W.; Wande, I.N. (Buletin Udayana Mengabdi, 2022)
Immunomodulators act as immunostimulants and immunosuppressants, so can maintain immunity. During the Covid-19 pandemic, the elderly was at high risk of being infected with SarCoV2, so it necessary to maintain the elderly immunity with socializing the use of natural immunomodulators and providing supplements to the elderly in Ketewel Village. After obtaining permission from the Village Head, the activities will be carried out in August 2021. Starting with the socialization of natural immunomodulators, followed by the distribution of vitamin supplements. The activity was attended by 72 people consisting of 29 men (40.3%) and 43 women (59.7%). All elderly (100%) used natural ingredients but did not know their function for immunity. The high use of natural materials was due to the fact that it integrated into the daily life in the village. However, when asked about the term "natural immunomodulator" only 6 people (6.3%) knew about it, this was due to the level of the elderly knowledge and had never socialized. Furthermore, the elderly was distributed supplements in the form of multivitamins. The activity well done with 72 participants, of which 100% used natural ingredients but only 6.3% knew the term "natural immunomodulators". Keywords: Natural immunomodulator, Elderly in Ketewel, Vitamin supplementation